Introducing a common currency in West Africa - Ozommah Ebubechukwu Daniel McJoel (2019)
The Economic Community of West African States (ECOWAS is a regional institution comprising of fifteen nations. It emerged on May 28, 1975 in Lagos Nigeria. One of the reasons behind its establishment is to ensure the existence of a single currency in the region. The desire to integrate the region into one economic bloc that will lead to the circulation of a single currency has been in the agenda of various regional heads of states conferences. However, it was discovered that colonial loyalty and the long existing monetary cooperation of Francophone nations with France was a strong impediment for the proposal which has an optimum target; likewise, member states have not been able to meet the set of convergence criteria which led to delays and shift of dates in establishing a common currency. In addition, there is a lack of political will and fear of domination among ECOWAS member states. To solve this problem, it was agreed in April 2000 in Accra Ghana, a two-fast track approach strategy should be adopted for the realization of a single currency. For the first track, the nonWest African Economic and Monetary Union (WAEMU) were to form a second monetary union called the West African Monetary Zone (WAMZ) by July 2005, which comprises mainly of Anglophone nations, with the second track being the subsequent merging of WAEMU and WAMZ to form a single currency union in the region. This research work examines the political constraints behind the constant shifting of dates for ECOWAS single currency integration, the obstacles faced, and other unforeseen circumstances that have contributed to the delay from the target dates shifting from 2003 to 2005, 2009, 2015 and 2020 at present. The research is qualitative in nature as such document analysis was adopted. The finding will suggest ways for accelerating the plan into action to ensure the new target will not lapse as before.